PENGARUH MEDIA SOSIAL DALAM MENINGKATKAN KESADARAN MENGENAI KESEHATAN MENTAL REMAJA: SEBUAH TINJAUAN LITERATUR SISTEMATIS - Permatasari, Desi (Al Ihsan Smart Cendekia, 2024)
Adolescent mental health is an important issue of global concern. Social media, which has become an integral part of adolescent life, has the potential to be a tool to raise awareness of mental health. This article aims to analyze the influence of social media in raising awareness of adolescent mental health through a systematic literature review (SLR). Literature searches were conducted on leading databases such as PubMed, Scopus, and Google Scholar using the keywords